(untitled) (Journal of Misan Researches, 2021)
The research discusses the religious changes brought about by Queen Mary I (1553-1558) in the English Church in order to return it to Catholicism as it was during the reign of her grandfather, King Henry VII (1485-1509), canceling all the measures taken against her during the reign of her father, King Henry VIII (1509-1547) and her brother, King Edward VI (1547-1553)